COVID-19 in Children: Respiratory Involvement and Some Differences With the Adults - Jurado Hernández, Jenny Libeth; Álvarez Orozco, Iván Francisco (Frontiers in Pediatrics, 2021)
The coronavirus disease 2019 (COVID-19) represents a health problem with a multidimensional impact and heterogeneous respiratory involvement in children, probably due to the interaction between different and complex mechanisms that could explain its variable degrees of severity. Although the majority of reports reveal that children develop less severe cases, the number of patients is increasing with more morbidity. Most serious respiratory manifestations are acute respiratory distress syndrome (ARDS) and pneumonia. By understanding the key aspects that differentiate pediatric and adult respiratory compromise by COVID-19, we can improve our knowledge, thus decreasing the negative impact of the disease in the pediatric population. In this mini review we summarize some of the mechanisms and findings that can distinguish adult and pediatric COVID-19 and respiratory involvement, taking into account some issues related to the physiopathology, diagnosis, clinical and paraclinical presentation, severity, treatment, and control of the disease.